Pemberian Mulsa Organik dan Pemangkasan Cabang Terhadap Pertumbuhan Dan Hasil Tanaman Semangka (Citrullus vulgaris Schard) Varietas F1 Punggawa - Gisela Jeanca Betra; Heti Herastuti; Tutut Wirawati (AGROISTA : Jurnal Agroteknologi, 2022)
Watermelon (Citrullus vulgaris Schard) is a horticultural commodity rich in nutrients that are beneficial to human health. One of the efforts to increase watermelon productivity is by applying organic mulch and pruning the branch. This research was held in July-October 2022 at the Garden of the Faculty of Agriculture, Universitas Pembangunan Nasional "Veteran" Yogyakarta, Wedomartani. Field experiments using the method compiled with Completely Randomized Block Design (CRD) factorial. The first factor was organic mulch with 3 levels, namely without mulch, rice straw, and husk rice. The second factor was pruning with 3 levels, namely without pruning, pruning leaving 2 branch, and pruning leaving 3 branch. The results showed that the best combination was mulching rice straw and pruning leaving 3 branch, there was an interaction between fruit weight per fruit and fruit weight per plant. Rice straw mulch gave the best results on plant length at 28 and 35 days after planting, number of male and female flowers, fruit diameter, fruit length, fruit weight per hectare, and sugar content. The pruning treatment leaving 3 branch gave the best results on plant lenght at 28 and 35 HST, the number of male and female flowers, fruit diameter, fruit length, fruit weight per hectare, and sugar content